Design and Applications of Integrated Transducers in Commercial CMOS Technology - Rawat, Udit; Anderson, Jackson D.; Weinstein, Dana (Frontiers in Mechanical Engineering, 2022)
Monolithic integration of Microelectromechanical Systems (MEMS) directly within CMOS technology offers enhanced functionality for integrated circuits (IC) and the potential improvement of system-level performance for MEMS devices in close proximity to biasing and sense circuits. While the bulk of CMOS-MEMS solutions involve post-processing of CMOS chips to define freely-suspended MEMS structures, there are key applications and conditions under which a solid, unreleased acoustic structure composed of the CMOS stack is preferred. Unreleased CMOS-MEMS devices benefit from lower barrier-to-entry with no post-processing of the CMOS chip, simplified packaging, robustness under acceleration and shock, stress gradient insensitivity, and opportunities for frequency scaling. This paper provides a review of advances in unreleased CMOS-MEMS devices over the past decade, with focus on dispersion engineering of guided waves in CMOS, acoustic confinement, CMOS-MEMS transducers, and large signal modeling. We discuss performance limits with standard capacitive transduction, with emphasis on performance boost with emerging CMOS materials including ferroelectrics under development for memory.